Analisis Perhitungan HPP Dengan Menggunakan Metode Full Costing Pada UMKM Warung Mie Ayam Bonar : Analysis of HPP Calculation Using the Full Costing Method in MSMEs of Bonar Chicken Noodle Warungs - Raihan Rivalsa Hadin; Pradana Erlangga; Muhammad Arman Saputra; Tiyo Aji Saputra; Yohanes Pati Kolin (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector require accurate  ) calculations as the basis for determining selling prices and making business decisions. However, many MSME owners have not fully allocated all production cost components, resulting in COGM calculations that do not accurately reflect the actual production costs. This study aims to analyze the calculation of the Cost of Goods Manufactured using the Full Costing method at Warung Mie Ayam Bonar, a culinary MSME located in West Jakarta. The study employed a descriptive research method with a case study approach. Data were collected through observation, interviews, and documentation of direct material costs, direct labor costs, and manufacturing overhead costs. The results indicate that the COGM calculated by the business owner was IDR 13,000 per serving, whereas the Full Costing method produced a COGM of IDR 15,000 per serving. The difference of IDR 2,000 per serving was due to the exclusion of asset maintenance and repair costs as part of manufacturing overhead costs. Therefore, the Full Costing method provides more comprehensive and accurate cost information, making it a more reliable basis for determining selling prices and managing production costs in MSMEs.